Vehicle classification method using compound kernel functions - Roxas, Edison A. (Animo Repository, 2018)
The focus of this paper is to explore the use of the Support Vector Machine (SVM) classifier. Though several literatures have already discussed the idea of using this method in vehicle classification, however, SVM accuracy is limited on the type of Kernel function used. Each Kernel functions has their own characteristics and limitations that is highly dependent on its parameter. Thus, in order to overcome these limitations, a method of compounding Kernel function for vehicle classification is hereby implemented. © 2018 IEEE.